Sams teach yourself Unix in 24 hours - Taylor, Dave, 1962- (Sams teach yourself., 2016)
In just 24 lessons of one hour or less, Sams Teach Yourself Unix in 24 Hours helps you get up and running with Unix and Unix-based operating systems such as Mac OS X and Linux. Designed for beginners with no previous experience using Unix, this book's straightforward, step-by-step approach makes it easy to learn. Each lesson clearly explains essential Unix tools and techniques from the ground up, helping you to become productive as quickly and efficently as possible. Step-by-step instructions carefully walk you through the most common Unix tasks. Practical, hands-on examples show you how to apply what you learn. Quizzes and excercises help you test your knowledge and stretch you skills. Notes and tips point out shotcuts and solutions. -- Back cover.